Metal-supported zinc glutarate catalyst, preparation method and application in synthesis of carbon dioxide copolymer

Through the development of the metal load -type zinc acid zinc acid catalyst, the problem of lack of selectivity and activity in the synthesis of existing catalysts in the synthesis of carbon dioxide synthesis was solved, and efficient catalytic effects and recyclables were achieved.

CN119371647AActive Publication Date: 2025-01-28CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411761492.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-01-28
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

Existing catalysts have problems such as insufficient selectivity and activity, complex and expensive design, sensitive to water and oxygen, unecotchable and inconvenient use in the synthesis of carbon dioxide copolymers.

Method used

The development of a metal load -type zinc diexate catalyst can form a connecting key to the metal (such as Na, K, Li, Mg, Al) with the surface of the pent dioxate catalyst to achieve a uniform load of the metal. This catalyst improves catalytic activity and selectivity through dual metal coordination mechanism.

Benefits of technology

The activity and selectivity of catalysts have been improved, and excellent catalytic activity and high polycarbonate chain segments are maintained in a wide range. The cluster reaction is to prepare a multi -embedded conjugate cluster with a high molecular weight, and it is recyclable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, in particular to a metal-supported zinc glutarate catalyst, a preparation method thereof and application of the metal-supported zinc glutarate catalyst in synthesis of a carbon dioxide copolymer. The metal-supported zinc glutarate catalyst is characterized in that metal is supported on the surface of a zinc glutarate catalyst; the metal is selected from one or more of Na, K, Li, Mg and Al. According to the invention, the activity and selectivity of the catalyst are further improved and the polymerization efficiency is improved by utilizing the stabilizing effect of the metal on the carbonate intermediate in the polymerization process through a bi-metal synergistic coordination mechanism. Higher ether ester selectivity is realized, and excellent catalytic activity and high polycarbonate chain segment selectivity can be maintained in a wide range of catalyzing copolymerization reaction of an epoxy compound and carbon dioxide; the ternary polymerization reaction of epoxide, carbon dioxide and cyclic ester can be catalyzed by a one-pot method to obtain a multi-block copolymer; the chain link proportion can be adjusted by adjusting the monomer feeding proportion, the reaction temperature, the reaction pressure and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a metal-supported zinc glutarate catalyst, a preparation method and application thereof in the synthesis of carbon dioxide copolymers. Background Art

[0002] One of the most pressing challenges in environmental protection is to replace the widely used petroleum-derived polymers with biodegradable polymers. Carbon dioxide, as a greenhouse gas, is harmful to the climate. At the same time, it is also an abundant and cheap carbon source material. Therefore, it is an ideal method to prepare biodegradable polymers using carbon dioxide as a raw material, which is in line with the concept of green chemistry.

[0003] Since Inoue's pioneering work in 1969, the ring-opening copolymerization of epoxides with carbon dioxide (ROCOP) has been intensively studied. Currently, in industry, aliphatic polycarbonates are mainly used as low molecular weight polyols for the manufacture of polyurethanes due to their special mechanical and thermal properties. However, considering that polyurethanes are not completely biodegradable, they do not fully conform to the above sustainable strategies. Therefore, the introduction of rigid biodegradable segments to replace the rigid segments in traditional polyurethanes to obtain greener polymers has attracted attention.

[0004] The synthesis of such materials requires specific tandem polymerization strategies and appropriate segment selection. The current methods for introducing biodegradable rigid segments mainly include lactide (LA) ring-opening polymerization (ROP) and phthalic anhydride (PA) / propylene oxide (PO) ROCOP. Although many catalysts have been used alone for LA ROP or PO / CO2 ROCOP, only a few catalysts are active for both polymerization processes. The development of new catalyst systems, such as metal-based catalysts, Lewis acid-base catalysts, and organic catalysts, is of great help in the design and synthesis of the above-mentioned sustainable polymers, and is conducive to the synthesis of the above-mentioned ideal polymers. However, these types of catalysts are complex and expensive to design, and are sensitive to water and oxygen, and cannot meet the needs of industrial applications. The preparation process uses a large amount of organic solvents, which is not environmentally friendly, and the prepared catalysts need to be water-activated before use, which is inconvenient to use. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a metal-supported zinc glutarate catalyst, a preparation method and application in the synthesis of carbon dioxide copolymers, wherein the catalyst has high selectivity and catalytic activity.

[0006] To achieve the above object, the present invention provides a metal-supported zinc glutarate catalyst, wherein a metal is supported on the surface of the zinc glutarate catalyst; the metal is selected from one or more of Na, K, Li, Mg, and Al.

[0007] The metal forms a connection bond with the hydroxyl group or carboxyl group on the surface of the zinc glutarate catalyst, and is then loaded on the surface of the zinc glutarate catalyst.

[0008] The present invention provides a method for preparing the metal-supported zinc glutarate catalyst, comprising the following steps:

[0009] The zinc glutarate catalyst and the metal salt are reacted in an aqueous medium to load the metal on the surface of the zinc glutarate catalyst to obtain a metal-loaded zinc glutarate catalyst;

[0010] The metal salt is a chloride salt, a fluoride salt or a bromide salt of metal Na, K, Li, Mg or Al.

[0011] The present invention has no particular limitation on the source of the zinc glutarate catalyst, which may be commercially available or prepared by methods well known to those skilled in the art.

[0012] Preferably, the zinc glutarate catalyst is prepared by reacting glutaric acid and zinc oxide in a toluene solvent.

[0013] The reaction temperature is preferably 60-80° C., more preferably 70° C.; the reaction time is preferably 10-15 h, more preferably 12 h.

[0014] The present invention adopts water as a medium and uses an alkali metal salt aqueous solution to simultaneously realize post-modification and activation of zinc glutarate, so that the metal is uniformly loaded on the surface of the zinc glutarate catalyst, which is more environmentally friendly. At the same time, the prepared catalyst does not need to be activated by water.

[0015] The reaction temperature is 40-80° C., more preferably 60° C.; the reaction time is 6-12 h, more preferably 12 h.

[0016] The molar ratio of the zinc glutarate catalyst to the metal salt is preferably 1: 0.01-1.

[0017] Preferably, the reaction further comprises: high temperature heat treatment;

[0018] The temperature of the high temperature heat treatment is preferably 250-350° C., more preferably 300° C.; the time of the high temperature heat treatment is preferably 5-7 hours, more preferably 6 hours.

[0019] The high temperature heat treatment can remove excess water in the catalyst and activate the catalyst at the same time.

[0020] Preferably, the high temperature heat treatment further comprises: drying.

[0021] The present invention has no particular limitation on the drying method, which may be a drying method known to those skilled in the art, and vacuum drying is preferred.

[0022] The drying temperature is preferably 80-100° C., more preferably 125° C.; the vacuum drying time is 24-48 h, more preferably 24 h.

[0023] The above drying can completely remove the moisture in the catalyst to obtain a dry catalyst.

[0024] The present invention provides the use of the metal-supported zinc glutarate catalyst or the metal-supported zinc glutarate catalyst prepared by the preparation method as a catalyst in the synthesis of carbon dioxide copolymers.

[0025] Specifically, the present invention provides a method for preparing polycarbonate, comprising: using carbon dioxide, epoxy compound and cyclic ester as raw materials, and carrying out a polymerization reaction under the catalytic action of the above-mentioned metal-supported zinc glutarate catalyst or the metal-supported zinc glutarate catalyst prepared by the above-mentioned preparation method to obtain a carbon dioxide-epoxy compound-cyclic ester copolymer.

[0026] The molar ratio of the catalyst, the cyclic ester and the epoxy compound is preferably 1:(5-100):(100-1000), more preferably 1:(10-75):(400-600).

[0027] The present invention has no particular limitation on the epoxy compound, including but not limited to propylene oxide and the like.

[0028] The present invention has no particular limitation on the specific type of the cyclic ester, including but not limited to one or more of glycolide, lactide, and caprolactone.

[0029] The polymerization reaction temperature is preferably 50-120° C., and the polymerization reaction time is preferably 6-48 h.

[0030] Compared with the prior art, the present invention provides a metal-supported zinc glutarate catalyst, wherein a metal is supported on the surface of the zinc glutarate catalyst; the metal is selected from one or more of Na, K, Li, Mg, and Al.

[0031] The metal-supported zinc glutarate catalyst provided by the present invention further improves the catalyst activity and selectivity and improves the polymerization efficiency by utilizing the stabilizing effect of the metal on the carbonate intermediates during the polymerization process through a bimetallic coordinated coordination mechanism. Compared with the traditional zinc glutarate catalyst, it achieves a higher ether ester selectivity and exhibits special catalytic performance: it can maintain excellent catalytic activity and high polycarbonate segment selectivity in a wide range when catalyzing the copolymerization reaction of epoxy compounds and carbon dioxide; it can catalyze the ternary copolymerization reaction of epoxides, carbon dioxide and cyclic esters in a "one-pot method" to obtain multi-block copolymers; and the segment ratio can be adjusted by adjusting the monomer feed ratio, reaction temperature and reaction pressure.

[0032] Experimental results show that the molecular weight of the polyester material obtained by the terpolymerization of propylene oxide, carbon dioxide and lactide catalyzed by the metal-supported zinc glutarate catalyst can reach 210kDa. In addition, the supported ZnGA catalyst is recyclable, and its simple and low-cost preparation process is compatible with the manufacturing and processing methods of existing infrastructure. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of supported zinc glutarate catalyst and blended zinc glutarate catalyst;

[0034] Figure 2 The SEM-EDS images of supported zinc glutarate catalyst and blended zinc glutarate catalyst;

[0035] Figure 3 The infrared absorption spectrum (upper) and pXRD image (lower) of the supported zinc glutarate catalyst;

[0036] Figure 4 DOSY NMR diagram of the polycarbonate prepared in Example 1;

[0037] Figure 5 This is the DOSY NMR chart of the product prepared in Comparative Example 1. DETAILED DESCRIPTION

[0038] In order to further illustrate the present invention, the following is a detailed description in conjunction with the embodiments. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention.

[0039] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0040] Preparation of zinc glutarate:

[0041] 13.2 g of glutaric acid was added to 1000 mL of toluene solvent, and after stirring for 30 min, 8.1 g of zinc oxide was added, and the mixture was heated at 70° C. and stirred for 12 h to obtain a zinc glutarate catalyst.

[0042] Example 1

[0043] In a 1L flask, 10g of zinc glutarate catalyst and 0.29g of NaCl were added to 500mL of water, stirred in a 60°C water bath for 12h to achieve uniform loading, heated at 300°C in a muffle furnace for 6h, and finally dried at 90°C in a vacuum oven for 24h to obtain a supported zinc glutarate catalyst.

[0044] The supported catalyst (0.2 g) was added to the autoclave, 500 molar equivalents of propylene oxide (29.7 g), 50 molar equivalents of lactide (7.4 g), and 2 MPa of carbon dioxide was introduced. The temperature was raised to 70°C and the reaction was carried out for 24 hours to obtain a carbon dioxide-epoxide-cyclic ester copolymer. The polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain the product. Sampling was performed 1 The H NMR test showed that the polyester unit content was 61%, and the polycarbonate unit content was tested, with a molecular weight of 210 kDa and a PDI of 1.91.

[0045] Figure 1 The middle left figure is a schematic diagram of the above-mentioned supported zinc glutarate catalyst.

[0046] Figure 2 The lower middle figure is the SEM-EDS image of the above-mentioned supported zinc glutarate catalyst, and the upper figure is the SEM-EDS image of the blended zinc glutarate catalyst, in which the yellow element is zinc and the blue element is sodium. Figure 2 It can be seen that both catalysts exhibit a typical flake-like crystal structure, and the distribution of zinc and sodium in the supported catalyst overlaps and is evenly distributed on the catalyst crystal surface, while the NaCl / ZnGA mixture shows the opposite result.

[0047] Figure 3 The infrared absorption spectrum (upper) and pXRD pattern (lower) of the above-mentioned supported zinc glutarate catalyst are shown in Figure 1. Figure 3 It can be seen that the introduction of metal ions does not cause any phase change or structural deformation of the lattice.

[0048] Figure 4 is the DOSY NMR diagram of the polycarbonate obtained in this example, Figure 4 It can be seen that the supported catalyst can obtain copolymerization products.

[0049] Example 2

[0050] In a 1L flask, 10g of zinc glutarate catalyst and 0.29g of NaCl were added to 500mL of water, stirred in a 60°C water bath for 12h to achieve uniform loading, heated at 300°C in a muffle furnace for 6h, and finally dried at 90°C in a vacuum oven for 24h to obtain a supported zinc glutarate catalyst.

[0051] The supported catalyst (0.2 g) was added to the autoclave, 500 molar equivalents of propylene oxide (29.7 g), 25 molar equivalents of lactide (3.8 g), and 2 MPa of carbon dioxide was introduced. The temperature was raised to 70°C and the reaction was carried out for 24 hours to obtain a carbon dioxide-epoxide-cyclic ester copolymer. The polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain the material. Sampling was performed 1 The H NMR test showed that the polyester unit content was 39%, and the polycarbonate unit content was tested, with a molecular weight of 180 kDa and a PDI of 1.85.

[0052] Example 3

[0053] In a 1L flask, 10g of zinc glutarate catalyst and 0.29g of NaCl were added to 500mL of water, stirred in a 60°C water bath for 12h to achieve uniform loading, heated at 300°C in a muffle furnace for 6h, and finally dried at 90°C in a vacuum oven for 24h to obtain a supported zinc glutarate catalyst.

[0054] The supported catalyst (0.2 g) was added to the autoclave, 500 molar equivalents of propylene oxide (29.7 g), 12.5 molar equivalents of lactide (1.9 g), and 2 MPa of carbon dioxide was introduced. The temperature was raised to 70°C and the reaction was carried out for 24 hours to obtain a carbon dioxide-epoxide-cyclic ester copolymer. The polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain the material. Sampling was performed 1 The H NMR test showed that the polyester unit content was 19%, and the polycarbonate unit content was tested, with a molecular weight of 150 kDa and a PDI of 1.83.

[0055] Example 4

[0056] In a 1L flask, 10g of zinc glutarate catalyst and 0.38g of KCl were added to 500mL of water, stirred in a 60°C water bath for 12h to achieve uniform loading, heated at 300°C in a muffle furnace for 6h, and finally dried at 90°C in a vacuum oven for 24h to obtain a supported zinc glutarate catalyst.

[0057] The supported catalyst (0.2 g) was added to the autoclave, 500 molar equivalents of propylene oxide (29.7 g), 50 molar equivalents of lactide (7.4 g), and 2 MPa of carbon dioxide was introduced. The temperature was raised to 70°C and the reaction was carried out for 24 hours to obtain a carbon dioxide-epoxide-cyclic ester copolymer. The polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain the material. Sampling was performed 1 The H NMR test showed that the polyester unit content was 23%, and the polycarbonate unit content was tested, with a molecular weight of 160 kDa and a PDI of 2.36.

[0058] Example 5

[0059] In a 1L flask, add 10g zinc glutarate catalyst and 0.48g MgCl2 to 500mL water, stir in a 60°C water bath for 12h to achieve uniform loading, heat in a muffle furnace at 300°C for 6h, and finally place in a vacuum oven at 90°C for 24h to obtain a supported zinc glutarate catalyst.

[0060] The supported catalyst (0.2 g) was added to the autoclave, 500 molar equivalents of propylene oxide (29.7 g), 50 molar equivalents of lactide (7.4 g), and 2 MPa of carbon dioxide was introduced. The temperature was raised to 70°C and the reaction was carried out for 24 hours to obtain a carbon dioxide-epoxide-cyclic ester copolymer. The polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain the material. Sampling was performed 1 H NMR test showed no polyester unit, the polycarbonate unit content was 99%, and only a trace amount of polyether was present. The molecular weight was measured to be 150 kDa and the PDI was 1.56.

[0061] Example 6

[0062] In a 1L flask, 10g zinc glutarate catalyst and 2.9g NaCl were added to 500mL water, stirred in a 60°C water bath for 12h to achieve uniform loading, heated in a muffle furnace at 300°C for 6h, and finally dried in a vacuum oven at 90°C for 24h to obtain a supported zinc glutarate catalyst.

[0063] The supported catalyst (0.2 g) was added to the autoclave, 500 molar equivalents of propylene oxide (29.7 g), 50 molar equivalents of lactide (7.4 g), and 2 MPa of carbon dioxide was introduced. The temperature was raised to 70°C and the reaction was carried out for 24 hours to obtain a carbon dioxide-epoxide-cyclic ester copolymer. The polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain the material. Sampling was performed 1The H NMR test showed that the polyester unit content was 76%, and the polycarbonate unit content was tested, with a molecular weight of 85 kDa and a PDI of 1.89.

[0064] Example 7

[0065] In a 1L flask, add 10g zinc glutarate catalyst and 0.58g NaCl to 500mL water, stir in a 60°C water bath for 12h to achieve uniform loading, heat in a muffle furnace at 300°C for 6h, and finally dry in a vacuum oven at 90°C for 24h to obtain a supported zinc glutarate catalyst.

[0066] The supported catalyst (0.2 g) was added to the autoclave, 500 molar equivalents of propylene oxide (29.7 g), 50 molar equivalents of lactide (7.4 g), and 2 MPa of carbon dioxide was introduced. The temperature was raised to 70°C and the reaction was carried out for 24 hours to obtain a carbon dioxide-epoxide-cyclic ester copolymer. The polymer was added to ethanol (200.0 g) for precipitation, filtered, and the filter cake was collected and dried to obtain the material. Sampling was performed 1 The H NMR test showed that the polyester unit content was 46%, and the polycarbonate unit content was tested, with a molecular weight of 163 kDa and a PDI of 2.32.

[0067] Comparative Example 1

[0068] 10g zinc glutarate catalyst and 0.29g NaCl were added to a mortar and ground for 20min to ensure uniform mixing. The blended catalyst (0.2g) was added to the autoclave, 500 molar equivalents of propylene oxide (29.7g), 50 molar equivalents of lactide (7.4g), and 2MPa of carbon dioxide was introduced. The temperature was raised to 70°C and the reaction was carried out for 24h to obtain a carbon dioxide-epoxide-cyclic ester copolymer. The polymer was added to ethanol (200.0g) for precipitation, filtered, and the filter cake was collected and dried to obtain the material. Sampling was performed 1 H NMR test showed that the polyester unit content was 41%, and the polycarbonate unit content was tested, with a molecular weight of 135 kDa and a PDI of 3.41, showing an obvious double peak. Characterization using DOSY technology proved that it was not a copolymer, but a mixture of PLA homopolymer, PPC homopolymer and a copolymer of the two. The results are as follows Figure 5 shown.

[0069] Figure 1 The middle right picture is a schematic diagram of the blended zinc glutarate catalyst.

[0070] Figure 2 The upper middle picture is a SEM-EDS combined image of the blended zinc glutarate catalyst, in which yellow represents zinc element and blue represents sodium element. Figure 5is the DOSY NMR diagram of the product obtained in Comparative Example 1, Figure 5 It can be seen that the diffusion coefficient of the product obtained by the blended catalyst is different from that in Example 1, and no copolymerization product is obtained.

[0071] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A metal-supported zinc glutarate catalyst, wherein a metal is supported on the surface of the zinc glutarate catalyst; the metal is selected from one or more of Na, K, Li, Mg, and Al.

2. A method for preparing a metal-supported zinc glutarate catalyst, comprising the following steps: The zinc glutarate catalyst and the metal salt are reacted in an aqueous medium to load the metal on the surface of the zinc glutarate catalyst to obtain a metal-loaded zinc glutarate catalyst; The metal salt is a chloride salt, a fluoride salt or a bromide salt of metal Na, K, Li, Mg or Al.

3. The preparation method according to claim 2, characterized in that: The reaction temperature is 40-80° C., and the reaction time is 6-12 hours.

4. The preparation method according to claim 2, characterized in that: The molar ratio of the zinc glutarate catalyst to the metal salt is 1: 0.01~1.

5. The preparation method according to claim 2, characterized in that: After the reaction, the following steps are further included: high temperature heat treatment; The temperature of the high temperature heat treatment is 250-350° C., and the time of the high temperature heat treatment is 5-7 hours.

6. The preparation method according to claim 5, characterized in that: The high temperature heat treatment further includes: drying.

7. The preparation method according to claim 6, characterized in that: The drying is vacuum drying; The drying temperature is 80-100° C., and the vacuum drying time is 24-48 hours.

8. The preparation method according to claim 2, characterized in that: The zinc glutarate catalyst is prepared by reacting glutaric acid and zinc oxide in a toluene solvent.

9. Use of the metal-supported zinc glutarate catalyst according to claim 1 or the metal-supported zinc glutarate catalyst prepared by the preparation method according to any one of claims 2 to 8 as a catalyst in the synthesis of carbon dioxide copolymers.

10. A method for preparing polycarbonate, comprising: Carbon dioxide, epoxy compound and cyclic ester are used as raw materials, and copolymerization reaction is carried out under the catalytic action of the metal-supported zinc glutarate catalyst according to claim 1 or the metal-supported zinc glutarate catalyst prepared by the preparation method according to any one of claims 2 to 8 to obtain a carbon dioxide-epoxy compound-cyclic ester copolymer.

Citation Information

Patent Citations

  • Preparation method of bimetallic MOF catalyst material

    CN117417535A

  • Catalyst for catalyzing copolymerization of carbon dioxide and epoxypropane as well as preparation method and application of catalyst

    CN118325061A

  • Composite zinc dicarboxylate catalyst and application thereof in catalytic synthesis of carbon dioxide-based polycarbonate

    CN118878805A

  • Copolymer comprising alkylene carbonate and method of preparing same

    US20030013840A1